Pengembangan LKPD berbasis Masalah pada Mata Pelajaran Instalasi Penerangan Listrik - Erik Okta Marizon; Aslimeri Aslimeri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research is motivated by a number of things including the limitations of supporting books for students, so that the use of supporting books for electric lighting installation subjects is still not effective, and also students still have difficulty mastering learning material properly. The purpose of this study was to produce valid and practical problem-based worksheets for the Class XI TITL Electrical Lighting Installation subject at SMK Negeri 5 Padang. The research method used is R&D (research and development). This research model is 4-D (Define, design, Development, disseminate). Data was collected using LKPD validation and practicality instrument sheets, LKPD validity questionnaires and LKPD practicality questionnaires. The subject of this study was problem-based worksheets for electrical lighting installations, with research respondents from class XI TITL students and teachers for the subject of electrical lighting installations. The questionnaire used in this study was in the form of a Likert scale with a score of 1 to 5. The LKPD media validator confirmed that the LKPD validation value was very valid. One teacher's practicality test resulted in a very practical score, and the practicality assessment of 32 students resulted in a very practical score. With this problem-based LKPD for the subject of Electrical Lighting Installation is very valid and practical so that it is suitable for use by both teachers and students during the learning process.